Drugi prispevek k poznavanju razširjenosti metuljev (Lepidoptera) subpanonskega dela slovenske Štajerske - Lesar, Tone (Acta entomologica slovenica (Ljubljana), 2006)
85 butterfly and moth species are listed, found in the subpannonian part of Slovene Štajerska expectantly (74) or unexpectantly (8) according to the Red List (Carnelutti 1992a, b), as well as 3 species not listed in the Red List. Presented are also 20 species from the adjacent pre-alpine area that could be found in the forthcoming investigations. First data for 36 species in the Slovene Štajerska are published, and for 36 species additional data are presented beside already published ones. 13 species are listed without new data. Five protected species give the region its value for nature-conservation.
Keywords: entomologija; favna; metulji; Slovenia; Slovenija